(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa - 2. La strategia elvetica per fare fronte alla pandemia e le osservazioni da parte della Conferenza Episcopale Svizzera - 3. La situazione italiana di fronte alla pandemia e le scelte in campo medico. I limiti all’autodeterminazione attraverso la proposta di introdurre l’obiezione di coscienza - 4. Conclusioni. Switzerland and Italy: triage and intensive medicine solutions in comparison ABSTRACT: Italy and Switzerland are two very different countries. This diversity is particularly evident in the health sector, not only in terms of its organization and management, but above all in the different approach that each country has with regard to the health of its members. The exaltation of therapeutic self-determination by Switzerland clashes with the medical paternalism to which Italy remains nostalgically linked, despite the fact that the needs of Italian society have changed profoundly. However, the dramatic choices to which the spread of Covid-19 has led have created the conditions for an inevitable reversal of the trend on the part of Italy and its approach to Swiss policies in terms of defending the freedom of choice of the individual.